Body composition and risk of vascular‐metabolic mortality risk in 113 000 Mexican men and women without prior chronic disease - Friedrichs, LG; Wade, R; Alegre‐Díaz, J; Herrington, W; Collins, R; Peto, R; Clarke, R; Emberson, JR (American Heart Association, 2023)
Background: Body‐mass index is the sum of fat mass index (FMI) and lean mass index (LMI), which vary by age, sex, and impact on disease outcomes. We investigated the separate and joint relevance of FMI and LMI with vascular‐metabolic causes of death in Mexican adults.